2023
DOI: 10.1001/jama.2023.17465
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to CPAP Treatment and the Risk of Recurrent Cardiovascular Events

Manuel Sánchez-de-la-Torre,
Esther Gracia-Lavedan,
Ivan D. Benitez
et al.

Abstract: ImportanceThe effect of continuous positive airway pressure (CPAP) on secondary cardiovascular disease prevention is highly debated.ObjectiveTo assess the effect of CPAP treatment for obstructive sleep apnea (OSA) on the risk of adverse cardiovascular events in randomized clinical trials.Data SourcesPubMed (MEDLINE), EMBASE, Current Controlled Trials: metaRegister of Controlled Trials, ISRCTN Registry, European Union clinical trials database, CENTRAL (Cochrane Central Register of Controlled Trials), and Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…Although the Coronary Drug Project recognized an “excess prevalence of baseline risk factors in the group of poor adherers,” in our study, the group with poor adherence did not exhibit a higher baseline cardiovascular risk profile. In addition, we controlled adherence analyses for time-dependent confounding factors such as body mass index and excessive daytime sleepiness.…”
contrasting
confidence: 69%
See 1 more Smart Citation
“…Although the Coronary Drug Project recognized an “excess prevalence of baseline risk factors in the group of poor adherers,” in our study, the group with poor adherence did not exhibit a higher baseline cardiovascular risk profile. In addition, we controlled adherence analyses for time-dependent confounding factors such as body mass index and excessive daytime sleepiness.…”
contrasting
confidence: 69%
“…In Reply Dr Finucane’s Letter highlights the potential underestimation of adherence bias in our study . We acknowledge that on-treatment analysis is not protected against selection bias.…”
mentioning
confidence: 84%
“…Despite this consistent evidence, recent RCTs 5961 investigating the effect of CPAP on different fatal and non-fatal CV events were negative 27 . These findings were supported by a recent individual meta-analysis of these studies 62 , although a post-hoc on-treatment analysis suggested a protective effect of good adherence to CPAP and reduced risk of MACE 62 . A careful investigation of the limitations in these trials 29 has suggested that patient selection and treatment adherence may have played an important role on explaining differences between RCTs and observational studies.…”
Section: Discussionmentioning
confidence: 73%
“…To the Editor In a recent meta-analysis, Sánchez-de-la-Torre and colleagues found that “adherence to CPAP [continuous positive airway pressure] was associated with a reduced MACCE [major adverse cardiac and cerebrovascular event] recurrence risk, suggesting that treatment adherence is a key factor in secondary cardiovascular prevention in patients with OSA [obstructive sleep apnea].” The authors acknowledged that “selection bias” may have affected their results, adjusted for several covariates, then asserted that the “results of this meta-analysis provide a rigorous basis for recommendations about the types of patients with OSA and established cardiovascular disease most likely to benefit from CPAP treatment…”…”
mentioning
confidence: 99%